Does case misclassification threaten the validity of studies investigating the relationship between neck manipulation and vertebral artery dissection stroke? Yes - Paulus, Jessica K. (Chiropr Man Therap, 2016)
BACKGROUND: For patients and health care providers who are considering spinal manipulative therapy of the neck, it is crucial to establish if it is a trigger for cervical artery dissection and/or stroke, and if it is, the magnitude of the risk. DISCUSSION: We discuss the biological plausibility of how neck manipulation could cause cervical artery dissection. We also discuss how case misclassification threatens the validity of influential published studies that have investigated the relationship between neck manipulation and dissection. Our position is supported by the fact that the largest epidemiologic studies of neck manipulation safety with respect to neurological outcomes have relied on International Classification of Diseases-9 codes for case identification. However, the application of these codes in prior studies failed to identify dissections (rather than strokes in general) and so conclusions from those studies are invalid. CONCLUSION: There are several methodological challenges to understanding the association between neck manipulation and vertebral artery dissection. Addressing these issues is critical because even a modest association between neck manipulation and cervical artery dissection could translate into a significant number of avoidable dissections given the widespread use of neck manipulation by providers from various backgrounds. We believe that valid case classification, accurate measurement of manipulative procedures, and addressing reverse causation bias should be top priorities for future research.